Τhe cognitive grounds of Hobbes’ Leviathan - Tsampazis, Nick (Dia-noesis: A Journal of Philosophy, 2024)
Hobbes is inspired by the mechanistic materialism of his time but is not convinced by the validity of empirical knowledge. There is no truth outside language. His own scientific method produces true propositions through rigorous logical processing of both lingual and empirical material. Leviathan is a direct product of this method as applied to the field of politics.